The accountability of NGOs - Creencia, Florida V. (Philippine Journal of Public Administration, 1994)
As early as the 1970s, the World Bank observed that the benefits derived from development loans did not accrue to people who were supposed to benefit from them. To correct this, the World Bank initiated a strategy of requiring that nongovernmental organizations (NGOs) be tapped as implementors of projects funded by loans through agreements it entered with the government. In turn, the government required nongovernmental organizations (NGOs) to enter into memoranda of agreement (MOAs), which identified the outputs expected by government organizations (GOs) for NGOs to accomplish as well the manner such accomplishments were to be evaluated. Auditing of NGOs is usually done by a special audit team (SAT), which looks into the compliance by NGOs with the provisions of the MOA and not the rules and regulations of the GOs. Based on the evaluation of assistance to selected NGOs, it is believed that there is a need to strengthen the NGOs-GOs accountability.